Analisis Kualitas dan Kadar Aflatoksin Jagung pada Pengeringan dengan Udara Alamiah - Jefrianus Nino (Savana Cendana, 2018)
Corn is a staple food for the majority of people in the East Nusa Tenggara Province, which corn is familiar to the East Nusa Tenggara’s peoples and planted for a long time ago. High production of corn can cause problem in post-harvest handling in terms of drying. Drying carried out by the community has not been well designed affect to degradation of the corn qualities. In addition to quality degradation there is also damage caused by the high moisture content in shelled corn that make them could be attack by fungi (Aspergillus flavus) to produced the aflatoxin. Aim of this study was to analyze the quality and content of corn aflatoxin in drying with natural air. The methods include drying corn with batch drying type, analysis of aflatoxin levels and the quality of carbohydrates, proteins and fat. In drying with an ambient at 30°C temperature and 75% relative humidity (RH) using batch drying type, not affect to decrease the aflatoxin level and corn quality.